2018
DOI: 10.3390/molecules23040868
|View full text |Cite
|
Sign up to set email alerts
|

Production of Flocculants, Adsorbents, and Dispersants from Lignin

Abstract: Currently, lignin is mainly produced in pulping processes, but it is considered as an under-utilized chemical since it is being mainly used as a fuel source. Lignin contains many hydroxyl groups that can participate in chemical reactions to produce value-added products. Flocculants, adsorbents, and dispersants have a wide range of applications in industry, but they are mainly oil-based chemicals and expensive. This paper reviews the pathways to produce water soluble lignin-based flocculants, adsorbents, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 147 publications
1
55
0
Order By: Relevance
“…There had been recent interest in modifying biomaterials such as starch, chitosan, and cellulose to develop environmentally friendly flocculants and dispersants, and few studies have focused on clay mineral suspensions or mineral unit operations such as flotation, as was discussed earlier . Hasan and Fatehi assessed two kraft lignin‐acrylamides with different molecular weights and observed that more quantities of polymer were adsorbed on kaolinite than on bentonite surfaces.…”
Section: Future Developmentsmentioning
confidence: 99%
“…There had been recent interest in modifying biomaterials such as starch, chitosan, and cellulose to develop environmentally friendly flocculants and dispersants, and few studies have focused on clay mineral suspensions or mineral unit operations such as flotation, as was discussed earlier . Hasan and Fatehi assessed two kraft lignin‐acrylamides with different molecular weights and observed that more quantities of polymer were adsorbed on kaolinite than on bentonite surfaces.…”
Section: Future Developmentsmentioning
confidence: 99%
“…This effect could possibly be caused by lignosulfonates acting as dispersant of the plant fibers and debris present in the crude juice. Lignosulfonates are in some applications used as dispersant of particles (Chen et al, 2018). The problem was solved by a mild centrifugation (called a clearing) of the juice prior to the precipitation.…”
Section: Initial Experimentsmentioning
confidence: 99%
“…[2][3][4] Lignin, an amorphous heteropolymer, is insoluble in water and has a limited reactivity. 5,6 It mainly comprises methoxylated phenylpropanoid (guaiacyl and syringyl) subunits that provide lignin with an energy density of 30% higher than that of polysaccharide polymers. 1,7 Lignin can be an alternative product to petroleum feedstocks for producing different chemicals.…”
Section: Introductionmentioning
confidence: 99%